Development of High Performance Liquid Chromatography-Tandem Mass Spectrometry Method for the Detection of Tulathromycin in Swine Plasma - Xian-hui HUANG; Yong-da ZHAO; Li-min HE; Zi-sen LIANG; Li-li GUO; Zhen-ling ZENG; Zhang-liu CHEN; Min ZHANG; Bing-hu FANG (Journal of Integrative Agriculture)
An accurate and precise method for the determination of tulathromycin in swine plasma was developed and validated. Plasma samples were analyzed by high-performance liquid chromatography with tandem mass spectrometry detection (HPLC-MS/MS) using electrospray ionization (ESI). Tulathromycin was extracted from plasma by precipitation with acetonitrile and separated using a Phenomenex Luna 5 μm C18 column (150 mm×2.0 mm) at a flow rate of 0.25 mL min−1. Solvent A consisted of 0.002 mol L−1 ammonium acetate and formic acid (999:1, v/v), and solvent B was acetonitrile. The mass spectrometer was operated in the selected-ion mode with atmospheric pressure chemical ionization to monitor the respective MH+ ions, namely, m/z 577.3 for tulathromycin and m/z 679.3 for the internal standard roxithromycin. The calibration curves were linear in a dynamic range of 2.0-500 ng mL−1 on the column. The accuracy was ranged from 95.25 to 109.75%, and the precision was ranged from 2.81 to 7.72%. The recoveries measured at 3 concentration levels (20, 250, and 500 ng mL−1) were higher than 98%. The method described above is efficient, and has the required accuracy and precision for rapid determination of tulathromycin in plasma. The method was applied to study the pharmacokinetics of tulathromycin in swine, and tulathromycin demonstrated a rapid absorption, wide distribution, and slow elimination after intramuscular administration.